1965
DOI: 10.1002/pssb.2220100231
|View full text |Cite
|
Sign up to set email alerts
|

Optical Absorption of Cu‐Centers in Alkali Halides

Abstract: I t is sho\\n from optical absorption nieasurements that under X-ray irradiation a t low temperatures Cu+ ions in Cu-doped KCI, KBr, and K I crystals trap electrons and holes. During this process Cu" and Cute centers are formed, which may be compared with Ag" and Ag++ centers in alkali halides. In the case of the Cut+ centersthesymmetryof the surrounding halogen ions is lowered by a Jahn-Teller distortion. This distortion, however, is different from that of the Ag++ centers studied by Delbecq, Hayes, O'Brien, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

1966
1966
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(40 citation statements)
references
References 19 publications
6
34
0
Order By: Relevance
“…The existence of both considered models in Cu-doped alkali-halides has been discussed in works [6,[10][11][12]. In our opinion, both of these models can be realized also in CsBr:Cu and CsBr:CuBr 2 crystals.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The existence of both considered models in Cu-doped alkali-halides has been discussed in works [6,[10][11][12]. In our opinion, both of these models can be realized also in CsBr:Cu and CsBr:CuBr 2 crystals.…”
Section: Discussionmentioning
confidence: 77%
“…Specifically, the emission in this band is weakly excited in the fundamental absorption range (6.2-8.3 eV) and is more effectively excited in the wide band peaked approximately at 4.5-5.1 eV which strongly overlap with the low-energy absorption band of Cu + ions. Most probably, this excitation band related to the formation of Cu 0 state [10] corresponds to the charge transfer transition (CTT) between the ground state of Cu 0 ions and bottom of conductive band. The emission band peaked at 3.08 eV at 10 K, related to the luminescence of excitons localized around Cu + ions, is excited mainly in the range of 5.5-6.2 eV (Fig.…”
Section: Luminescence Of Cu + Ionsmentioning
confidence: 99%
“…Indeed this has been reported by Nagasaka et al [12] who find the highest energy excitation band a t 7.5 eV at LHeT. It should be noted that Oggioni and Scaramelli [4] and KrMzig et al [5] do not mention the presence of this band in KC1 : Cu because their measurements do not extend into the vacuum ultraviolet.…”
Section: Interpretation Of Luminescence and Liietime Measurementsmentioning
confidence: 66%
“…Seitz interpretcd the Cu+ transition to be analogous to the Ag+ transition on the basis of early work on NaCl : Cu by MacMahon 131 who reported a small oscillator strength ( k 0.001) and a strong temperature dependence of the absorption strength in agreement with that reported for Ag+. More recently Oggioni and Scaramelli [a] and Kriitzig et al [5] reported an order of magnitude larger oscillator strength for Cu+ in the potassium halides over that of Ag+ in the same crystals. A very small temperature dependence of the oscillator strengths for Cu+ in KC1, KBr and K I was explained by Kratzig et al on the basis of an off-center model of Cu+.…”
Section: Introductionmentioning
confidence: 98%
“…Cu þ emission has also been used in thermo luminescence dosimetry phosphors such as LiF: Mg, Cu, P [16], Li 2 B 4 O 7 : Cu [17,18] Cu þ emission can also be used as blue component of full color electro luminescent display devices [19,20]. However, more common valency of copper is 2 þ , and the methods for incorporating monovalent Cu have not been systematically worked out e.g., in several works results on Cu þ emission in alkali halides have been mentioned [21][22][23][24][25][26][27][28][29][30], but the procedure adopted for incorporating Cu in monovalent form has not been given. Several authors on the other hand, mention that incorporation of Cu þ can be difficult [31].…”
Section: Introductionmentioning
confidence: 97%